2007
DOI: 10.1515/znb-2007-0223
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Tropane Alkaloid Pattern in Two African Convolvulaceous Species. Phytochemistry and Chemotaxonomy of the Convolvulaceae, Part 20 [1]

Abstract: An unusual and complex tropane alkaloid pattern has been detected in the root bark of Astripomoea malvacea and in the whole plant of Falkia repens (Convolvulaceae) by GC-MS analysis. The specific profile of both species is characterized by the presence of aliphatic 3-acyloxytropanes/-nortropanes (exclusively in A. malvacea; predominantly in F. repens in cooccurrence with a few aromatic as well as arylalkyl acyl congeners). The principal alkaloid of A. malvacea, astrimalvine A N-oxide [3β -(3-tigloyloxy-2-methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The dried extract is dissolved in chloroform or dichloromethane and washed with alkalised water. After evaporation and solution in a GC-compatible solvent, e. g. methanol or hexane, this crude extract is subjected to GC-MS. For example, Jenett-Siems and colleagues [23] elucidated 74 tropane derivatives in an extended study on Merremia alkaloids and listed their fragmentation patterns in GC-MS. Ott and colleagues observed heterogeneous mixtures of compounds with typical tropane fragmentation pattern by GC-MS (quadrupole mass spectrometer) in crude plant extracts of African Convolvulaceae species [24]. They isolated tigloyl-und methylbutyryl esters of both ␣-and ␤-3-hydroxytropanes and confirmed the structures by 1 H-NMR and 13 C-NMR.…”
Section: Alkaloids In Plant Extractsmentioning
confidence: 92%
“…The dried extract is dissolved in chloroform or dichloromethane and washed with alkalised water. After evaporation and solution in a GC-compatible solvent, e. g. methanol or hexane, this crude extract is subjected to GC-MS. For example, Jenett-Siems and colleagues [23] elucidated 74 tropane derivatives in an extended study on Merremia alkaloids and listed their fragmentation patterns in GC-MS. Ott and colleagues observed heterogeneous mixtures of compounds with typical tropane fragmentation pattern by GC-MS (quadrupole mass spectrometer) in crude plant extracts of African Convolvulaceae species [24]. They isolated tigloyl-und methylbutyryl esters of both ␣-and ␤-3-hydroxytropanes and confirmed the structures by 1 H-NMR and 13 C-NMR.…”
Section: Alkaloids In Plant Extractsmentioning
confidence: 92%
“…During our continuous studies on secondary metabolites of the Convolvulaceae, this plant family has been shown to produce a plethora of tropane alkaloids, especially 3-tropanols and their esters (e. g. [1, 2]), as well as some 3,6-disubstituted tropanes [3] or the polyhydroxylated calystegines [4]. This underlines the chemotaxonomic relationship with their sister family Solanaceae where the biosynthetic pathway of tropane alkaloids is well investigated.…”
Section: Introductionmentioning
confidence: 98%
“…Representatives of tropane N ‐oxide alkaloids have been also found in nature, e.g. 3α‐tigloyloxytropane N ‐oxide from Physalis alkekengi , darlingine N ‐oxide from Darlingia darlingiana , catuabine E N ‐oxide from Erythroxylum vacciniifolium , (+)‐anhydroecgoine methyl ester N ‐oxide from Erythroxylum emarginatum , astrmalvine A N ‐oxide from Astripomoea malvacea , 7α‐hydroxycatuabine H N ‐oxide and vaccinine B N ‐oxide from E. vacciniifolium Mart. (Erythroxylaceae).…”
Section: Introductionmentioning
confidence: 99%